2017
DOI: 10.2147/ijwr.s69126
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the biodynamic wine sector

Abstract: The wine industry is currently shifting toward more sustainable production practices. Due to the growing globalized wine market and the increasing environmental impacts, producers have begun to pay more attention to organic and biodynamic products. Using a systematic literature review, this review aims to investigate the biodynamic production system in the viticulture and winemaking process. In particular, the review examines, 1) the biodynamic practice and its main characteristics including the certification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
0
47
0
1
Order By: Relevance
“…In recent years, both winegrowers and consumers have shown steadily growing interest in organic wine production (Mann et al, 2012;Willer et al, 2013). In the course of this development, biodynamic wine production especially is receiving increasing attention (Castellini et al, 2017), because winegrowers have reported remarkable positive influences of biodynamic practices on soil quality, grapevine development, plant health and wine quality (Preston, 2008;Masson, 2009;Meissner, 2015). In biodynamic agriculture, in addition to compost fertilization and cover crops, preparations of specific fermented plant materials are used to enhance soil fertility and microbial diversity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, both winegrowers and consumers have shown steadily growing interest in organic wine production (Mann et al, 2012;Willer et al, 2013). In the course of this development, biodynamic wine production especially is receiving increasing attention (Castellini et al, 2017), because winegrowers have reported remarkable positive influences of biodynamic practices on soil quality, grapevine development, plant health and wine quality (Preston, 2008;Masson, 2009;Meissner, 2015). In biodynamic agriculture, in addition to compost fertilization and cover crops, preparations of specific fermented plant materials are used to enhance soil fertility and microbial diversity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Biodynamic production is instead a comprehensive organic farming method still founded on a "voluntary" basis, without any public intervention. 5 In this perspective, the biodynamic winemaking process is more restrictive than the organic one, with even stricter limits. 6 As an example, Demeter ® (the most widespread voluntary biodynamic certification in Europe and the rest of the world) provides guidelines for the biodynamic winemaking process: 7 exclusive use of indigenous yeasts; no added yeast nutrients; minimal use of sulfites; exclusive use of permitted adjuvants and additives.…”
mentioning
confidence: 99%
“…-Complejidad: frente a la elaboración convencional, la elaboración de vino con métodos ecológicos puede alcanzar altos niveles de complejidad, tanto en el viñedo como en la bodega, puesto que se pierde el nivel de control que, gracias a los avances técnicos, se obtiene mediante la primera (Bouzdine-Chameeva y Krzywoszynska, 2011) [19]. -Mayores costes: aunque existe bastante variabilidad en los costes de producción asociados, debido a las condiciones del viñedo y al tipo de gestión, en diferentes estudios se indica que los viticultores orgánicos experimentan mayores costes operativos asociados (1) con un mayor uso de mano de obra, (2) y por el uso de insumos alternativos a los convencionales para las labores de prevención (Castellini, 2017) [20]. -Inversión en normalización: se realiza un esfuerzo adicional en tiempo y recursos financieros para obtener (y mantener) la certificación de vino ecológico, con unéxito comercial todavía bastante relativo e incierto (Delmas y Grant 2014) [21].…”
Section: Situación En Castilla Y Leónunclassified